2023
DOI: 10.1039/d2an01771g
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabutylammonium-chloride-glycerol of deep eutectic solvent functionalized MnO2: a novel mimic enzyme for the quantitative and qualitative colorimetric detection of l-cysteine

Abstract: L-Cysteine is a common amino acid, which plays an important role in human livelihood and production. Therefore, a novel method for simultaneous quantitative and qualitative determination of L-Cysteine by colorimetric...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In Figure D, the addition of 50 μM l -Cys presented the highest absorbance change except GSH and AA. Apparently, this is a common disadvantage of colorimetric methods, and the published literature had similar results . Adding masking agents or combining with high-performance liquid chromatography (HPLC) could eliminate the effects of GSH and AA .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure D, the addition of 50 μM l -Cys presented the highest absorbance change except GSH and AA. Apparently, this is a common disadvantage of colorimetric methods, and the published literature had similar results . Adding masking agents or combining with high-performance liquid chromatography (HPLC) could eliminate the effects of GSH and AA .…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, this is a common disadvantage of colorimetric methods, and the published literature had similar results. 49 Adding masking agents or combining with high-performance liquid chromatography (HPLC) could eliminate the effects of GSH and AA. 50 The results indicated the good anti-interference ability and excellent selectivity of the sensing assay based on Ni-ZIF-67/ AuAg/AgCl for L-Cys detection.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Chen and colleagues effectively solved the problem via modifying MnO 2 nanosheets with DESs, thus improving the efficiency of the photoreaction. 54 Liu et al reported that DESs are good heat enhancers and the hydrogen bond network can enhance the heat transfer capacity of NPs, 55 which provides a possible strategy for optimizing the photothermal performance of Mn-based NPs. The above-mentioned results indicate that the unique functions of ILs and DESs are expected to provide ideas for improving the light utilization efficiency of Mn-based NPs.…”
Section: Synthesis Of Mn-based Npsmentioning
confidence: 99%
“…1,2 Reportedly, abnormal levels of L-cysteine can assist in diagnosing various diseases such as hypogenesis, skin lesions, hepatic injury, decreased hematopoiesis, AIDS, Alzheimer's disease, Parkinson's, etc. [3][4][5][6] Moreover, L-cysteine plays an important role in medicine and the food industry, like being used as a food additive 7,8 and detoxifying heavy metals and radioactive drugs. 9 Considering the aforementioned properties, the detection of Lcysteine is of great signicance for human health and food quality assurance.…”
Section: Introductionmentioning
confidence: 99%